Synthesis of Biologically Relevant β‐N‐Glycosides by Biphasic Epoxidation‐Aminolysis of D‐Glycals. Issue 16 (27th April 2020) - Santiago, Cintia C.; Lafuente, Leticia; Ponzinibbio, Agustín
Abstract: Several β‐ N ‐glycosides were obtained upon a simple and efficient two‐step methodology. First, α‐1, 2‐anhydrosugars were prepared diastereoselectively by the oxidation of 3, 4, 6‐tri‐O‐benzyl‐D‐glucal under biphasic conditions (CH2 Cl2 /water) using dimetyldioxirane (DMDO) generated in situ from oxone/acetone mixture and amphiphilic imidazolium ionic liquid (DodMImBF4 ) as phase transfer catalyst. Immediately, β‐ N ‐glycosides were synthesized in good yields by aminolysis of these α‐1, 2‐anhydrosugars using CH3 CN as solvent. The overall process allows stereoselective generation of biologically relevant carbohydrate derivatives. Abstract : Herein we present a simple, efficient and reliable method to access β‐ N ‐glycosides from D‐glycals. This novel two‐step methodology for the preparation of these biologically relevant compounds consists of an epoxidation reaction followed by a nucleophilic opening using different kinds of amines. In all cases high stereoselectivity and good yields were achieved.